POTENTIAL OF CIRCULAR ECONOMY IMPLEMENTATION IN MANAGING PLASTIC WASTE IN KABUPATEN BENGKALIS - Hasima Sima; Hutomo Atman Maulana (Universitas Malikussaleh, 2023)
The problem faced by Kabupaten Bengkalis is the amount of waste, especially plastic waste, which continues to increase and causes accumulation in final processing sites and temporary shelters. This research aims to determine the implementation of a circular economy in plastic waste management, the most effective waste management model for the management of plastic waste in, the obstacles in the management of plastic waste, and the solutions that can be used to manage plastic waste in the circular economy. This research uses a descriptive qualitative research method. In this research, the data collection techniques are interviews, observation, and visual image techniques. The result of this research is that the manifestation of a circular economy with the 5R principle (Reduce, Reuse, Recycle, Recovery, and Revalue) still requires time and a gradual process. This is related to the behavior and mindset of the community in handling and managing plastic waste, which hasn't started from sorting waste from home.